Effects of Monosodium Glutamate Oral Administration on LH and Testosterone Levels in Serum of Adult Male Rats (Rattus norvegicus) - Annisa, Riska; Djati, Moch. Sasmito; Rahayu, Sri (Graduate School, Universitas Brawijaya, 2019)
This study aims to determine the effect of monosodium glutamate on LH and testosterone levels in serum of adult male rats (Rattus norvegicus). A total of 12 male Wistar-strained rats divided into three groups with 4 rats per group. Control group was given distilled water, while M1 was given MSG at a dose of 4mg g-1 BW for 15 days and M2 was given MSG at a dose of 4 mg g-1BW for 45 days. All substances were given orally. At the end of the study, rats were sacrificed with a dislocation to draw blood from the heart. Then, the blood was incubated at room temperature to obtain serum. Serum was used to analyze LH and testosterone levels using the ELISA kit. Data were analyzed using one way ANOVA (p ≤ 0.05) with SPPS 16.0 for windows. The results showed that serum LH levels after MSG treatments for 45 days was significantly decreased compared with the control. The serum testosterone levels M2 was significantly difference with the control group (p ≤ 0.01). This study predicts that monosodium glutamate have a direct and indirect effect on male reproductive organs. Keywords: Luteinizing hormone, Monosodium glutamate, testosterone.